PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS SMA NEGERI 2 LENGAYANG KABUPATEN PESISIR SELATAN - Zaiti, Nurmai; Nova, Sari (JURNAL BUANA, 2024)
The research objective was to determine the effect of applying the Snowball Throwing cooperative learning model to the geography learning outcomes of class XI IPS students at SMA Negeri 2 Lengayang, Pesisir Selatan Regency. This research uses a quasi-experimental type of experimental method. The design used in this study is the Pretest – Posttest Control Group Design. From the T test that has been carried out, the results for Tcount are 3.703 while Ttable is 2.024, so in this test Tcount ≤ Ttebel, then the Snowball Throwing type cooperative learning model has an effect on student learning outcomes in geography learning class XI IPS at SMAN 2 Lengayang. The N-Gain test in this study was for the control class, with a test value of 55% in the moderate or quite effective category, while for the experimental class, a test value of 76% was obtained in the high or very effective category. So that the application of the snowball throwing cooperative learning model has an effect on geography learning outcomes. Keywords: Snowball Throwing. Experiment. Learning outcomes